From Wi-Fi to Li-Fi: A comprehensive review of integration strategies - Hasanudin, Afif Hakim; Zainal, Izzah Hazirah; Abdul Mutalip, Zaiton; Jasman, Faezah; Wan Hassan, Wan Hafiza (Wydawnictwo SIGMA-NOT, 2023)
Li-Fi, also known as light fidelity, is a promising technology for the wireless communication sector in the future. Similar to Wi-Fi, it is a fully networked and bidirectional technology that offers incredibly high speeds. However, there are some limitations associated with Li-Fi technology, such as its reliance online of sight between the transmitter and receiver, its susceptibility to interference from external light sources, and its short coverage area, particularly indoors. Therefore, to overcome these issues, proposed integrating Li-Fi with other hybrid wireless communication technologies. This article discusses the integration of Li-Fi with Wi-Fi and cellular networks in V2X (vehicle-to-everything) communication, satellite communication systems, and Industrial IoT (IIoT). In the future, as the speed of light is significantly faster than other transmission methods, Li-Fi technology has the potential to revolutionize data access speeds for devices.